2020
DOI: 10.1093/geroni/igaa043
|View full text |Cite
|
Sign up to set email alerts
|

Caring for Older Adults With Vision Impairment and Dementia

Abstract: Background and Objectives Dementia and vision impairment (VI) are common among older adults but little is known about caregiving in this context. Research Design and Methods We used data from the 2011 National Health and Aging Trends Study, a nationally representative survey of Medicare beneficiaries, linked to their family/unpaid helpers from the National Study of Caregiving. VI was defined as self-reported blindness or diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(36 citation statements)
references
References 29 publications
4
32
0
Order By: Relevance
“…Indeed, the toll of caring for older adults with VIs is enormous and many unpaid caregivers report significant consequences for their own quality of life. The identified barriers for unpaid family caregiver quality of life include depressive symptoms, life satisfaction, caregiver burden, emotional distress, social concerns, psychological concerns, stress, mental health, physical health, strain, and number of hours of care provided to the older adult with VI (Bambara et al, 2009; Horowitz et al, 2004; Varadaraj et al, 2020; Watson, 2001; Whitson et al, 2011). These barriers negatively impacted the quality of life of unpaid caregivers of older adults with VI that were included in the studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the toll of caring for older adults with VIs is enormous and many unpaid caregivers report significant consequences for their own quality of life. The identified barriers for unpaid family caregiver quality of life include depressive symptoms, life satisfaction, caregiver burden, emotional distress, social concerns, psychological concerns, stress, mental health, physical health, strain, and number of hours of care provided to the older adult with VI (Bambara et al, 2009; Horowitz et al, 2004; Varadaraj et al, 2020; Watson, 2001; Whitson et al, 2011). These barriers negatively impacted the quality of life of unpaid caregivers of older adults with VI that were included in the studies.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Whitson et al (2011) proposed a series of multimodal communication techniques (e.g., written instructions or audio messages) and related interventions to maximize convenience (e.g., in-home visits, synchronization with other health services, or transportation) for unpaid caregivers of older adults with VIs. Furthermore, Varadaraj et al (2020) discussed outreach programs or interventions focusing on caregiving training and other support services. Other proposed interventions included better engagement and support for family caregivers of people with VIs in the health care system, support services, and interventions targeted toward improving quality of life and related outcomes (Bambara et al, 2009; Horowitz et al, 2004; Watson, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…Our scoping review also demonstrates the almost complete lack of studies focused on the impact on carers, with only one qualitative study and one quantitative study addressing this topic. 3,13 Many studies reporting comments from carers were about the impact of VI on those with dementia, rather than the impact of VI on themselves as part of their caring role. Therefore, an important area of further study would be to investigate the impact of VI on carers of those with dementia, including consideration of health outcomes of carers.…”
Section: Discussionmentioning
confidence: 99%
“…There were only two studies (one qualitative and one quantitative) that speci cally investigated the added impact of VI to dementia on carers, both in a community setting 3,13 (Table 3 and Table 4). A UK qualitative study reported negative impacts on carers of those with dementia and VI including negative emotions and loss of hobbies 14 .…”
Section: Impact Of Visual Impairment On Carers Of Older People With D...mentioning
confidence: 99%
See 1 more Smart Citation